2019
DOI: 10.1113/jp276849
|View full text |Cite
|
Sign up to set email alerts
|

Physiological basis of brief vigorous exercise to improve health

Abstract: This review considers the physiological basis of brief vigorous exercise to improve health, with a focus on cardiorespiratory fitness (CRF) and glycaemic control, and the potential underlying mechanisms involved. We defined 'brief' as a protocol lasting ࣘ15 min including warm-up, cool-down and recovery, and involving a total of ࣘ5 min of 'vigorous' exercise, which was classified as meeting or exceeding the lower end of the range for this relative intensity as per the criteria from the American College of Sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 48 publications
(69 reference statements)
1
45
0
Order By: Relevance
“…Several studies have shown that HIIT can elicit various physiological adaptations that are linked to improved health outcomes [ 18 20 ]. However, to date, data on the feasibility and efficacy of low-volume HIIT applied to severely obese individuals at increased cardiometabolic risk are sparse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that HIIT can elicit various physiological adaptations that are linked to improved health outcomes [ 18 20 ]. However, to date, data on the feasibility and efficacy of low-volume HIIT applied to severely obese individuals at increased cardiometabolic risk are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying reasons why obese individuals do not participate in sufficient PA are manifold but—as in the general population—the most commonly cited barrier is “lack of time” [ 17 ]. Hence, the development of less time-consuming exercise modalities has recently gained increasing attention [ 18 ]. In this context, high‐intensity interval training (HIIT) has emerged as a time-efficient and effective exercise strategy for achieving health‐relevant benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding aerobic exercise, the study found that aerobic exercise improves glycemic control, [93][94][95][96][97][98][99][100][101][102][103][104] insulin sensitivity, [105][106][107] insulin action, 70 body composition, 99 quality-of-life, 108 physical capacity, 99 nerve function, 109 functional capacity, 110 and cardiorespiratory fitness, 101,111 reduces insulin resistance, 97,112,113 insulin levels, 96 lipid profile, 97 BP, 97,100 cardiovascular risk, 106 hemoglobin A1c (HbA1c) levels, 95,111 and waist circumstances, 100 and modulates inflammatory cytokine levels 113 and adipocytokines 113 in T2DM patients.…”
Section: Management Of T2dmmentioning
confidence: 99%
“…MOC is used for both sports and medical purposes as a determinant of physical efficiency or as a risk indicator of health and longevity (Kodama et al, 2009). Many researchers noted that high intensity work of aerobic character (despite of short muscle stimulus) causes recruitment of all muscle fibers in the working muscle that leads to convincing changes in mitochondrial content of all active muscle and growth of oxidative abilities of working muscles (Gibala, Little, 2019;MacInnis, Gibala, 2016). After 60 days of trainings reliably athletes of the main group increased AnT work capacity and oxygen consumption by 22.7 and 14.5 % respectively (Tables 4 and 5).…”
Section: Resultsmentioning
confidence: 99%